2015
DOI: 10.11611/jmer400
|View full text |Cite
|
Sign up to set email alerts
|

Narsi̇st Ki̇şi̇li̇k Eği̇li̇mleri̇ İle Kurumsal Bağlilik Düzeyleri̇ Arasindaki̇ İli̇şki̇ni̇n Anali̇zi̇

Abstract: Yö ön ne et ti im m v ve e E Ek ko on no om mi i A Ar ra aş şt tı ır rm ma al la ar rı ı D De er rg gi is si i --C Ci il lt t: :1 13 3 S Sa ay yı ı: :1 1 ( (O Oc ca ak k 2 20 01 15 5) ) --D Do oi i: : h ht tt tp p: :/ // /d dx x. .d do oi i. .o or rg g/ /1 10 0. .1 11 16 61 11 1/ /J JM ME ER R4 40 00 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…It has been determined that the narcissistic behaviors of physical education teachers who are graduates of postgraduate education are at a higher level than physical education teachers who have undergraduate degrees. Similar to the research findings, Cihangiroğlu et al (2015) stated that the total narcissism score was highest in the final students and then in the 5th-grade students. It can be said that many factors may be effective in the clarification of the narcissistic personality traits of students who have come to the end of a long and difficult education process.…”
Section: Dıscussıon and Resultssupporting
confidence: 86%
“…It has been determined that the narcissistic behaviors of physical education teachers who are graduates of postgraduate education are at a higher level than physical education teachers who have undergraduate degrees. Similar to the research findings, Cihangiroğlu et al (2015) stated that the total narcissism score was highest in the final students and then in the 5th-grade students. It can be said that many factors may be effective in the clarification of the narcissistic personality traits of students who have come to the end of a long and difficult education process.…”
Section: Dıscussıon and Resultssupporting
confidence: 86%
“…From another point of view, it can be interpreted that narcissistic personality trait tendencies, which are stronger in the first year of study, can have decreased as a result of students' exhaustion and frustration in the middle of their education life. Cihangiroğlu et al (2015) found that levels of narcissism differed statistically significantly in terms of the year of study (p=0.017) and that this difference occurred because of the difference between students in their first and fourth year of study and students in their fourth and fifth year of study (4).…”
Section: Discussionmentioning
confidence: 99%
“…Due to these characteristics, they are accepted in organizations. However, as narcissism increases, these positive effects are replaced by harmful, destructive, and corrosive consequences (Cihangiroğlu, Teke, Uzuntarla and Uğrak, 2015). One of the questions to be answered in the research is how narcissistic leadership affects creative employee performance.…”
Section: Conclusion and Discussionmentioning
confidence: 99%